Optical and structural characterization of CdS/ZnS and CdS:Cu2+/ZnS core–shell nanoparticles. (19th November 2013) - Murugadoss, G.; Kumar, M. Rajesh
ABSTRACT Core‐shell CdS/ZnS (Zn 0.025‒0.125 M) and CdS:Cu2+(1%)/ZnS nanoparticles were successfully synthesized using a chemical method. X‐ray diffraction (XRD), high‐resolution transmission electron microscopy (HR TEM), photoluminescence (PL) and UV/Visible (UV/Vis) techniques were used to characterize the novel CdS/ZnS and CdS:Cu2+/ZnS core–shell nanoparticles. All absorption peaks of the synthesized samples were highly blue‐shifted from the bulk CdS and ZnS. Very narrow and symmetric PL emission was observed in the yellow region for core–shell CdS/ZnS. Furthermore, the PL emission of CdS/ZnS was tuned into orange region by incorporate the Cu ion into the core CdS lattice. Copyright © 2013 John Wiley & Sons, Ltd.